2019
DOI: 10.1021/acs.jproteome.9b00318
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Zika and Japanese Encephalitis Virus NS5 Interactomes

Abstract: Mosquito-borne flaviviruses, including dengue virus (DENV), Japanese encephalitis virus (JEV), and Zika virus (ZIKV), are major human pathogens. Among the flaviviral proteins, the nonstructural protein 5 (NS5) is the largest, most conserved, and major enzymatic component of the viral replication complex. Disruption of the common key NS5-host protein–protein interactions critical for viral replication could aid in the development of broad-spectrum antiflaviviral therapeutics. Hundreds of NS5 interactors have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 76 publications
3
14
2
Order By: Relevance
“…In addition to capsid and NS4B, several novel ZIKV NS5 binders were recently identified in these proteomics surveys. Among these, multiple members of the PAF1C complex (Leo1, CDC73, CTR9 and PAF1), confirming similar observations previously made on DENV-NS5 by the Gamarnik group [53] and recently confirmed by others [54]. Importantly, while these interactions appear highly conserved among DENV, ZIKV, JEV and WNV-NS5s, a moderate and reciprocal effect on viral replication was observed upon gene silencing (2-fold increase and 2-fold decrease for ZIKV and JEV infectivity, respectively) [41,54].…”
Section: Flavivirus Interactions With the Cellular Proteomesupporting
confidence: 88%
See 1 more Smart Citation
“…In addition to capsid and NS4B, several novel ZIKV NS5 binders were recently identified in these proteomics surveys. Among these, multiple members of the PAF1C complex (Leo1, CDC73, CTR9 and PAF1), confirming similar observations previously made on DENV-NS5 by the Gamarnik group [53] and recently confirmed by others [54]. Importantly, while these interactions appear highly conserved among DENV, ZIKV, JEV and WNV-NS5s, a moderate and reciprocal effect on viral replication was observed upon gene silencing (2-fold increase and 2-fold decrease for ZIKV and JEV infectivity, respectively) [41,54].…”
Section: Flavivirus Interactions With the Cellular Proteomesupporting
confidence: 88%
“…Among these, multiple members of the PAF1C complex (Leo1, CDC73, CTR9 and PAF1), confirming similar observations previously made on DENV-NS5 by the Gamarnik group [53] and recently confirmed by others [54]. Importantly, while these interactions appear highly conserved among DENV, ZIKV, JEV and WNV-NS5s, a moderate and reciprocal effect on viral replication was observed upon gene silencing (2-fold increase and 2-fold decrease for ZIKV and JEV infectivity, respectively) [41,54]. Further mechanistic studies suggest that PAF1 might be recruited by NS5 to reduce expression of interferon-stimulated genes and therefore dampen immune responses [41].…”
Section: Flavivirus Interactions With the Cellular Proteomesupporting
confidence: 88%
“…Thus, HSP90 inhibitors phenocopy JAK/STAT antagonism by flaviviruses, a similarity of function that we confirmed with side-by-side analyses. Our data revealed for the first time that flavivirus NS5 binds HSP90 to mediate broad STAT inhibition, which extends upon descriptive reports from other groups that identified JEV, DENV, and ZIKV NS5 interaction with HSP90, but did not define the relevance of this interaction [39][40][41]. Several DENV proteins have also been shown to bind HSP90 [37].…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, flavivirus NS5 was shown to interact with some of the proteins that make up the Paf1 complex. It was found that inhibition of this complex increased infectivity of ZIKV and DENV but inhibited JEV thus showing that some host proteins interact differently with different flaviviruses [62]. Finally, NS5 is highly conserved among different flaviviruses [26,50,53,63], so identifying possible host protein interactions might prove an effective way to develop antivirals.…”
Section: Biochemical Studiesmentioning
confidence: 99%